Aspects of the volunteering experience associated with well‐being in older adults. (19th August 2020) - Jongenelis, Michelle I.; Pettigrew, Simone
Abstract: Issues addressed: While the psychological health benefits of older people's engagement in formal volunteering are well‐documented, there is limited research assessing how volunteering may produce these favourable outcomes. To guide the development of volunteer positions that optimise outcomes, this study examined (a) which aspects of the volunteering experience are most strongly associated with favourable psychological health among older adults and (b) whether relationships between these aspects and psychological outcomes are moderated by sociodemographic characteristics. Methods: A sample of 293 volunteers aged 60+ years (69% female, mean age = 73.33 years) completed measures assessing their engagement in volunteering, various aspects of their volunteer experience, and their psychological health. Results: Being adequately appreciated for one's contribution, perceived social and mental intensity of the volunteer role, and believing that others benefit from one's volunteering efforts were found to be associated with higher levels of psychological health. Conclusions: Ensuring the contributions of volunteers are explicitly recognised, providing opportunities for engagement in social and cognitive activities, and informing volunteers of the benefits others experience constitute potential means of enhancing volunteer outcomes and may assist with volunteer retention. So what?: This study builds upon the limited research assessing which aspects of the volunteering experience are most strongly associated with favourable psychological health among older adults. The findings point to the potential importance of four specific aspects of the volunteer experience in enhancing psychological health outcomes.